2009
DOI: 10.1002/chin.200944007
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Magneto‐Transport Properties of Polycrystalline YBa2 (Cu1‐xMx)3O7‐δ (M: B and Mn).

Abstract: Superconductors D 8000Magneto-Transport Properties of Polycrystalline YBa2(Cu1-xMx)3O7-δ (M: B and Mn). -The effect of chemical doping with B and Mn on the magnetic and transport properties of the YBa2Cu3O7-δ superconductor is investigated. The critical current density is significantly enhanced by Mn doping, especially at low temperatures for all applied magnetic fields. Boron-doping results in a considerable increase in the hysteresis width of magnetization and enhancement of the lower critical field. Resisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…[60][61][62][63][64][65] transparency and fl exibility. [ 66 ] Figure 1 c shows the currentvoltage ( I-V ) properties of the device with and without bending when the device was exposed to 365 nm UV light and in the dark, respectively, while Figure 1 d shows the photocurrent versus light intensities curves of the device under bending for different cycles. These results indicated that the fl exible device based on ZnO nanorods has a good electronic stability and mechanical robustness.…”
Section: Flexible Binary-oxide-based Pdsmentioning
confidence: 99%
“…[60][61][62][63][64][65] transparency and fl exibility. [ 66 ] Figure 1 c shows the currentvoltage ( I-V ) properties of the device with and without bending when the device was exposed to 365 nm UV light and in the dark, respectively, while Figure 1 d shows the photocurrent versus light intensities curves of the device under bending for different cycles. These results indicated that the fl exible device based on ZnO nanorods has a good electronic stability and mechanical robustness.…”
Section: Flexible Binary-oxide-based Pdsmentioning
confidence: 99%